Efektivitas Metode Presentasi terhadap Pemahaman Landasan Filosofis Pendidikan Mahasiswa Teknologi Pendidikan UPI - ., Eva Rofatun Nazwa; ., Reifa Aulia Nur Fauziah; ., Rifky Ismail Pratama; ., Soca Permana Bardian (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The presentation method is a method of presenting ideas in public by students individually or in groups. This research is motivated by student behavior during question and answer sessions or discussions where many students are just silent without expressing their opinions. This makes researchers interested in examining the effectiveness of the presentation method on the understanding of UPI Educational Technology students regarding the material Philosophical Foundations of Education. The research method used is pre-experimental designs with the type of one-group pretest-posttest design. The research sample was UPI Educational Technology students who were taking the philosophical foundation of education course as many as 15 people. The results showed that the presentation method was effective in improving the understanding of Educational Technology 2A students regarding the philosophical foundations of education with a difference in the average pre-test score of 38.00 and post-test of 61.33 where this figure had a significant increase of 0.001 through the t test that had been carried out.